Education Needs for Social License to Operate for Resource Industries - Agnieszka Czaplicka-Kotas (Communications of International Proceedings, 2025)
The Social Licence to Operate (SLO) is a crucial concept that enables companies to build and sustain relationships with stakeholders. In the literature, SLO is highlighted as a key element for obtaining acceptance and approval from stakeholders to proceed with business operations. However, emerging European legislative and non-legislative requirements related to sustainability, circularity, and the climate-energy transition are driving a redefinition of the SLO concept. These new requirements will particularly impact resource industries, which will need to adapt their entire value chains. This transformation will demand the development of new skills, knowledge, and competencies. Therefore, this article aims to examine the educational needs arising from these policy changes and to assess existing educational projects related to SLO tools and frameworks. For this purpose, the study analyzed the curricula of 73 innovation-education projects supported under the EIT RawMaterials framework, based on four key components of the SLO: stakeholder mapping and engagement capabilities; measurement of the social license to operate; development of social license strategies; and integration of international frameworks for SLO. The results indicate that educational efforts most often focus on stakeholder mapping, assessing stakeholder needs, and developing stakeholder monitoring frameworks, while the assessment of strategies and methods for stakeholder engagement measurement is less frequently addressed. Moreover, this underscores the need for developing new knowledge, skills, and competencies to meet the evolving legislative and non-legislative requirements related to SLO.
Keywords: social license to operate; stakeholder engagement; education; resource industries; environmental policy